Data privacy and GDPR handbook - Sharma, Sanjay (John Wiley & Sons, Inc., 2020)
"Maintaining the privacy of data pertaining to existing/potential customers, employees and vendors etc. is becoming a serious concern for senior management and boards of companies across all industries, sizes, scope and geographic footprints. The recently enacted Global Data Protection Regulation (GDPR) in Europe imposes stringent and elaborate requirements for any firm or organization conducting business in the EU, with fines for violations up to 5% of global revenue. Yet, business community's awareness of this law and other emerging data privacy requirements is lacking. A recent survey of firms in the UK suggests that only 40% of the firms are even aware of the law and their responsibilities. This lack of awareness is even more pronounced in the US. This book will address data privacy squarely and authoritatively. Book is divided into three sections: history and foundation of data privacy; necessary framework for ensuring data privacy in the US, Europe and across other major global jurisdictions; deconstruction of GDPR with a comprehensive framework for complying with it; and perspective on the future of data collection and privacy practices"--
Includes index. - Includes bibliographical references and index. - Description based on online resource, title from digital title page (viewed on December 21, 2020)
Keywords: European Parliament -- General Data Protection Regulation; Data protection -- Law and legislation -- European Union countries; BUSINESS & ECONOMICS; Corporate Governance; Data protection; Law and legislation; Computer security; Data protection; Privacy, Right of; European Union countries